Incentives for cocoa bean production in Ghana: Does quality matter? - Quarmine, W; Haagsma, R; Sakyi-Dawson, O; Asante, F.A; van Huis, A; Obeng-Ofori, D (Elsevier, 2012)
This paper investigates the institutional factors that constrain farmers’ incentives to enhance the quality of cocoa beans in Ghana. Data were collected at three levels of aggregation in the cocoa bean value chain: village, district, and national level. Multi-stage cluster sampling was employed to sample 120 farmers and 12 purchasing agents of licensed buying companies from 12 villages in Assin Foso, Suhum, Dormaa and Wasa Akropong cocoa districts. Convenience sampling was used to sample key informants from relevant organizations and service providers at district and national levels. The study revealed that, even though quality is important to all categories of actors in the cocoa sector, interactions among them are hampered by problems of information asymmetry that result especially in farmers evading recommended practices. While cocoa sector policies ensure the export of premium quality cocoa, policies have not sufficiently alleviated the information problem especially in the relation between farmers and cocoa purchasing agents. It explains why Ghanaian farms have not been able to reach their full potential to produce more than 1,000,000 metric tons of premium quality cocoa annually. Amongst other options, self-selection policies, such as quality testing with price premiums, are recommended for testing as potential incentive mechanisms that address information
Keywords: Value chain; Information asymmetry; Institutional experiments